Evaluation of inflammation-related genes polymorphisms in Mexican with Alzheimer’s disease: a pilot study - Toral-Rios, Danira; Franco-Bocanegra, Diana; Rosas-Carrasco, Oscar; Mena-Barranco, Francisco; Carvajal-García, Rosa; Meraz-Ríos, Marco Antonio; Campos-Peña, Victoria (Frontiers in Cellular Neuroscience, 2015)
Amyloid peptide is able to promote the activation of microglia and astrocytes in Alzheimer’s disease (AD), and this stimulates the production of pro-inflammatory cytokines. Inflammation contributes to the process of neurodegeneration and therefore is a key factor in the development of AD. Some of the most important proteins involved in AD inflammation are: clusterin (CLU), complement receptor 1 (CR1), C reactive protein (CRP), tumor necrosis factor α (TNF- α), the interleukins 1α (IL - 1α), 6 (IL-6), 10 (IL-10) and cyclooxygenase 2 (COX-2). In particular, COX-2 is encoded by the prostaglandin-endoperoxide synthase 2 gene (PTGS2). Since variations in the genes that encode these proteins may modify gene expression or function, it is important to investigate whether these variations may change the developing AD. The aim of this study was to determine whether the presence of polymorphisms in the genes encoding the aforementioned proteins is associated Mexican patients with AD. Fourteen polymorphisms were genotyped in 96 subjects with AD and the differences in allele, genotype and haplotype frequencies were analyzed. Additionally, an ancestry analysis was conducted to exclude differences in genetic ancestry among groups as a confounding factor in the study. Significant differences in frequencies between AD and controls were found for the SNP rs20417 within the PTGS2 gene. Ancestry analysis revealed no significant differences in the ancestry of the compared groups, and the association was significant even after adjustment for ancestry and correction for multiple testing, which strengthens the validity of the results. We conclude that this polymorphism plays an important role in the development of the AD pathology and further studies are required, including their proteins.